Psychosocial factors affecting class participation in virtual EFL environments in PINE major students at UPSE. - Rocafuerte Lindao, Edwin Fabián (2023)
The present research comes out with the idea to analyze how the students feel and what aspects are involved in this learning process during virtual EFL environments, applying a qualitative methodology to understand this complex area of human beings which are the psychological and social aspects affecting the learning process, the sample was PINE 2/1 students at UPSE who still work under this methodology. According to the findings of the research and focus groups, most students experience contrasting emotions during virtual classes, including stress, anxiety, and discouragement. On the other side, new issues are introduced, such as inadequate communication between teachers and peers, which is vitally needed for learners to stay focused on their objectives and motivated. Psychosocial factors are becoming more significant in education since they play a role in the learning process as a core part of encouraging students to succeed.